On the lower estimation of the rate of convergence in the local theorem - Gamkrelidze, N. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Г. Гамкрелидзе. Об одной нижней оценке для скорости сходимости в локальной теореме N. Gamkrelidzė. Apie vieną konvergavimo greičio apatinį įvertinimą lokalinėje teoremoje